THE DYNAMICS OF COOPERATION: A LONGITUDINAL STUDY IN FURNITURE BUSINESS NETWORKS - Wegner, Douglas; Rossi, Greice De; Scarano, Tiago Franquini (Contextus - Revista Contemporânea de Economia e Gestão, 2014)
Few studies on interorganizational networks (ION) consider the dynamic nature of cooperation and occurring changes over time. Based on this gap, we analyzed the changes between the years of 2004 and 2011 in two furniture business networks in the state of Rio Grande do Sul. To the network trajectory analysis, three variables were selected: cooperation management and results obtained by participants; relational environment and trust among participants and, external agents support. It was verified that managerial complexity and the critical events which occurred led to the closure of one network, despite the positive results networks achieved in 2004 and the development of a favorable relational environment among members. The other network had its cooperative activities reduced. A big challenge for the management of ION is to provide new benefits to the firms as entrepreneurs’ individuals interests change.